A novel copper (II) PAmPiCaT complex (cPAmPiCaTc) as a biologically potent candidate: A contraption evidence against methicillin-resistant Staphylococcus aureus (MRSA) and a molecular docking proof. Issue 5 (1st March 2019) - Nagendra Prasad, H.S.; Manukumar, H.M.; Karthik, C.S.; Mallesha, L.; Mallu, P.
Graphical abstract: A copper (II) complex of cPAmPiCaTc can damage the MRSA membrane and induce to repress the virulence determinants SarA and DFHR pave to evoke cellular events in regular to inhibit the growth and infection state which is hypothetically addressed with concern of future biomedical applications. Abstract: Increasing in the alarm against the resistant bacteria due to the failure of antibiotics, thereby the need of more efficiency/potent molecule to treat infections. In the present investigation, series of piperazine derivatives5(a-l) compounds were synthesized and they were characterised by different spectral techniques such as 1 H NMR, 13 C NMR, IR and LCMS. A novel copper complex (cPAmPiCaTc) was developed for the first time by using potent analog5e and characterized by IR and LCMS. The cPAmPiCaTc evaluated for antibacterial activity and showed excellent antimicrobial effect (12 ± 0.08 mm, ZOI) at MIC 20 µg/mL against MRSA compared to standard antibiotics streptomycin and bacitracin at MIC 10 µg/mL. The results show promising anti- staphylococcal action against MRSA which confirmed by membrane damage, bioelectrochemistry, gene regulation ( SarA and DHFR ), and in silico molecular docking studies. Further, the cPAmPiCaTc also showed excellent blood compatibility and this result pave the way for interesting metallodrug therapeutics in future against MRSA infections.